2007
DOI: 10.1007/s00383-006-1873-7
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral congenital diaphragmatic hernia and gastroschisis in a newborn: can low intrathoracic pressure prevent the pulmonary hypoplasia?

Abstract: Congenital diaphragmatic hernia (CDH) is associated with high mortality and morbidity due to pulmonary hypoplasia (PH) and persistent pulmonary hypertension (PPH). Bilateral CDH is extremely rare with poor prognosis. It is usually accepted that PH in CDH is due to the herniation of abdominal viscera in the thorax leading to compression of the lung and preventing the normal lung development. On the other hand, some authors suggest that the PH occurs independently from the intrathoracic pressure in foetuses with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Transgenic mutant gene knockout animals have been particularly helpful in establishing the biochemical regulation of airway development by demonstrating the necessary roles of certain growth and transcription factors [51,52]. In contrast, surgical models of modified lung development have permitted the biomechanical regulation of lung development to be elucidated [10,11,53]. Furthermore, human cases have provided vivid illustrations of the biomechanical regulators of lung growth (congenital laryngeal atresia, Potter's syndrome) [54,55].…”
Section: Understanding Of Lung Development Derives From a Variety Of mentioning
confidence: 98%
“…Transgenic mutant gene knockout animals have been particularly helpful in establishing the biochemical regulation of airway development by demonstrating the necessary roles of certain growth and transcription factors [51,52]. In contrast, surgical models of modified lung development have permitted the biomechanical regulation of lung development to be elucidated [10,11,53]. Furthermore, human cases have provided vivid illustrations of the biomechanical regulators of lung growth (congenital laryngeal atresia, Potter's syndrome) [54,55].…”
Section: Understanding Of Lung Development Derives From a Variety Of mentioning
confidence: 98%
“…Coexistence of CDH with abdominal defects has previously been reported in neonates with a septum transversum diaphragmatic defect, which leads to midline anomalies such as the pentalogy of Cantrell or CDH plus a large epigastric omphalocele without sterna or cardiac anomalies, or neonates who have omphalocele associated with a congenital intrapericardial diaphragmatic hernia [ 4 , 11 , 12 ]. CDH is also associated with abdominal wall defects in Fryns syndrome: an autosomal recessive syndrome that features multiple congenital anomalies including distal digital hypoplasia, coarse facies, abnormalities of the ears, and CDH [ 5 , 13 ]. Coexistence of CDH with abdominal wall defects has also been reported in non-syndromic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with both anomalies, underestimation of CDH or overestimation of the abdominal cavity volume can occur. There have been reports on diagnosis of CDH after abdominal wall closure or of CDH causing symptoms such as severe respiratory distress or circulatory instability after the abdominal wall defect is treated [ 11 , 13 , 14 ]. In our case 1, accurate prenatal diagnosis allowed successful treatment by establishing a silo at delivery, followed by surgical closure of the defects in the diaphragm and abdominal wall after stabilization of the patient’s general condition.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed presentation of right-sided CDH in association with neonatal group B streptococcalp neumonia is a well-recognizedentity [4][5]. Antenatal diagnosis of CDH is relatively easy and the sonographic signs of unilateral CDH are mediastinal shift, presence of intestine in the thorax, small abdominal circumference and polyhydramnios suffice [1][2][3][4][5][6][7][8][9][10]. Mediastinal shift is often the first abnormality observed.…”
Section: Discussionmentioning
confidence: 99%
“…Many additional abnormalities have been reported, such as trisomy 21, trisomy 13, tetrasomy 21, trisomy 8 and other structural abnormalities. Small rearrangements found in unrelated individuals have suggested that one or more genes significant for normal diaphragm development may reside in critical regions such as 15q26.2 [6][7][8][9][10]. In a study made by Furuta et al [ 3] reported the 11th recorded case of bilateral CDH.…”
Section: Discussionmentioning
confidence: 99%